An assessment of the utilization of Municipal Infrastructure Grant for sustainable service delivery and improved quality of life : a case study of the City of Tshwane Metropolitan Municipality, Gauteng Province, RSA - Singo, Takalani Aubrey (My University, 2012)
The study seek to analyze the role of the Local Government in distribution of equitable and basic needs to its community through efficient and effective service delivery through the utilization municipal infrastructure grant. Municipal service delivery is still a major concern in South Africa. In terms of the Constitution of South Africa (Act 106 of 1996), municipalities are the only spheres of government that are mandated for delivery of basic services such as water, sanitation, electricity, refuse removal, development and maintenance of community infrastructure, storm water, primary health and provision of better housing to the poorest of the poor. The new dispensation in 1994, necessitated the transformation of the municipalities towards service delivery. The apartheid system was characterized by inequities in terms of provision of sustainable needs to its communities. The service delivery was fragmented along racial lines. Blacks were largely excluded from better services, while the minority enjoyed the services of municipalities around the country. Various laws, policies were enacted to find ways of ensuring that municipalities are responsive to community’s demands and needs in an equitable manner. The White Paper on Local Government in 1998, outlined some strategies that needs to be followed for the Local Government to achieve its objective. The background of the study, problem statements highlighted the historical imbalances in the system and how it can be redressed to provide good governance at the local government. The research questions form the basis of the study. The questionnaire for data gathering were formulated in line with the research questionnaire. Municipalities are characterized by service backlog, lack of skills (administratively and technically), lack of transparency and accountability that contribute to major challenges faced by municipalities in service provision. The research methodology used in this study focused more on the qualitative to allow participants to express their feelings in a descriptive manner and less on the iv quantitative approach wherein figures were reflected in a form of tables and graphs . The provision of service, as a social phenomena focused on human beings as object of study. Ethical considerations were taken into account. Questionnaires were distributed to executive directors and officials in strategic positions of service delivery of City of Tshwane Metropolitan Municipality and also to SALGA, CoGTA and National Treasury. The aim of the questionnaire was to find out and assess the challenges faced by municipal officials on their day to day activities regarding the management and utilization of MIG in a responsible and accountable manner. Extensive literature review covered a range of books, journals, African National Congress (ANC) Manifesto, Reconstruction and Development Programme (RDP), White Paper, Discussion Documents and City of Tshwane’s Annual Reports, Service Delivery Strategies Reports and other related documents that advocate for service delivery challenges and its impact. The findings revealed that municipalities faced common challenges that impede on the progress of service delivery. Some of the challenges are beyond their control like the non-availability of government owned land. Most of municipalities are characterized by lack of funding, under-spending or over-spending. Media news regularly covers negative aspects such as corruption that occurs in municipalities and not positive issues of delivery of service. In the City of Tshwane Metropolitan Municipality, housing is still a major challenge. The ever increasing demand from communities also impact on the budget of the municipality. Immigration in Tshwane area have negative effect on service delivery, particularly the housing backlog and proper sanitation.
Thesis (M.Dev.) -- University of Limpopo, 2012
Keywords: Service delivery; Municipal Infrastructure Grant; Basic needs; Municipal government -- South Africa -- Gauteng; Municipal services -- South Africa -- Gauteng; Local government -- South Africa -- Gauteng